Experimental Study On Efficiency Of DC And AC Power Supply Travel Kit Using Solar Panel - Ab Aziz, Ab Wafi; Rahim, Norain; Mohd Tumari, Mohd Zaidi; Abdul Kadir, Ahmad Muzaffar; Abd Rashid, Wan Norhisyam; Ainol Bakri, Ainol Sheqal (Penerbit Universiti,UTeM, 2018)
The paper presents an experimental study on the efficiency of an assembly-kit of a standalone AC and DC power supply that is suitable for people who appreciate outdoor activities such as travel,jungle tracking,camping and so on with one major setback which is the limited electricity power source.The kit uses photovoltaic (PV) system to generate electricity from sunlight that will charge the controller to then stored generated energy in the battery.An inverter is used to convert DC power from battery to AC power for supplying power to AC appliances. Two places which are Bukit Beruang and Marina Beach in Melaka,Malaysia were chosen for the experiment to be conducted.Data of voltage produced by the PV system at these two places are taken and recorded.Charging handphone and power up lamp is used to test the DC and AC power consumption of the travel kit.Result obtained demonstrates the effectiveness of the travel kit in supplying AC and DC power for lite usage.